Cyrtodactylus saiyok sp. nov., a new dry evergreen forest-dwelling Bent-toed Gecko (Squamata: Gekkonidae) from Kanchanaburi Province, western Thailand - Panitvong, Nonn; Sumontha, Montri; Tunprasert, Jitthep; Pauwel, Olivier S. G. (Zootaxa, 2014)
We describe Cyrtodactylus saiyok sp. nov. from a dry evergreen forest on a limestone hill in Khao Krajae, Sai Yok District, Kanchanaburi Province, western Thailand. It is characterized by a maximal known SVL of 61.0 mm; 18–19 longitudinal rows of dorsal tubercles; 23 or 24 ventral scale rows between ventrolateral skin folds; a continuous series of enlarged femoro-precloacal scales, including 5 pore-bearing precloacal scales (males); no precloacal groove or depression; transversely enlarged subcaudal scales; a complete black nuchal loop; a W-shaped band above shoulders and 3–5 irregular, medially interrupted or not, black dorsal bands between limb insertions. Cyrtodactylus saiyok sp. nov. is the sixth reptile species that is possibly endemic to Sai Yok District.